Prospective Echocardiographic Evaluation of the Right Ventricle and Pulmonary Arterial Pressure in Hyperthyroid Patients - Gazzana, M. L.; Souza, J. J.; Okoshi, M. P. [UNESP]; Okoshi, K. [UNESP] (Elsevier, 2019)
Background: Pulmonary arterial hypertension (PAH) occurs in 35% to 65% of hyperthyroid patients. Despite this high frequency, only a few authors have examined the effects of hyperthyroidism treatment on PAH and the right ventricle. We evaluated the effects of hyperthyroidism and its reversal on cardiovascular structure and function using Doppler echocardiography. Methods: We prospectively evaluated 32 patients (42.5 ± 11.9 years old) with thyrotoxicosis. Exclusion criteria included previous cardiovascular disease. An echocardiogram was performed at the time of hyperthyroidism diagnosis and after normalisation of free thyroxine (T4) levels. Patients were divided into two groups according to the presence or absence of PAH at the diagnosis, or at two moments, before and after T4 normalisation. Results: Graves’ disease was the most frequent aetiology (75%) of hyperthyroidism. Pulmonary arterial hypertension was observed in 43.8% of patients. Free T4 concentration was higher in PAH than non-PAH patients. Free T4 normalised after 5 (2.0-10.5; median and percentiles) months of treatment. Cardiac chamber sizes and cardiac output were higher in PAH. Right ventricular (RV) systolic function was impaired in PAH. Cardiac output and free T4 (r = 0.42; p < 0.05) correlated with pulmonary artery systolic pressure (PASP). Cardiac chamber size, cardiac output, left ventricular ejection fraction, and PASP (34.0 ± 8.6 to 21.7 ± 4.5 mmHg) reduced after treatment. Right ventricular myocardial performance index and fractional area change improved after T4 normalisation. Conclusions: Pulmonary arterial hypertension is highly prevalent in hyperthyroid patients and is combined with increased cardiac chambers size and cardiac output, and impaired RV function. Cardiovascular changes are reversible after T4 normalisation in patients without cardiovascular disease.
Keywords: Cardiac remodelling; Echocardiography; Graves; Hyperthyroidism; Pulmonary hypertension; Right ventricle